Scan Test Coverage Improvement Via Automatic Test Pattern Generation (Atpg) Tool Configuration - Salehuddin, Muhammad Redzwan (2017)
The scan test coverage improvement by using automatic test pattern generation (ATPG) tool configuration was investigated. Improving the test coverage is essential in detecting manufacturing defects in semiconductor industry so that high quality products can be supplied to consumers. The ATPG tool used was Mentor Graphics Tessent TestKompress (version 2014.1). The study was done by setting up a few experiments of utilizing and modifying ATPG commands and switches, observing the test coverage improvement from the statistical reports provided during pattern generation process and providing relatable discussions. By modifying the ATPG commands, it can be expected to have some improvement in the test coverage. The scan test patterns generated were stuck-at test patterns. Based on the experiments done, comparison was made on the different coverage readings and the most optimized method and flow of ATPG were determined. The most optimized flow gave an improvement of 0.91% in test coverage which is acceptable since this method does not involve a change in design. The test patterns generated were converted and tested using automatic test equipment (ATE) to observe its performance on real silicon. The test coverage improvement using ATPG tool instead of the design-based method is important as a faster workaround for back-end engineers to provide high quality test contents in such a short product development duration.